Association of overweight/obesity and insulin resistance with activation of circulating innate lymphoid cells in women after gestational diabetes mellitus - Julia Sbierski-Kind; Julia Sbierski-Kind; Julia Sbierski-Kind; Julia Sbierski-Kind; Stephan Schlickeiser; Stephan Schlickeiser; Lorenzo Semeia; Lorenzo Semeia; Saori Harada; Saori Harada; Eleni Pappa; Eleni Pappa; et al. (Frontiers in Immunology)
IntroductionWomen with a history of gestational diabetes mellitus (GDM) are at high risk of developing prediabetes or type 2 diabetes later in life. Recent studies have highlighted the regulation and function of innate lymphoid cells (ILCs) in metabolic homeostasis. However, the multifactorial impact of both overweight/obesity and GDM on the immunological profile of circulating ILCs and the progression to prediabetes are not yet fully elucidated.MethodsBlood samples from 42 women with a history of insulin-treated GDM (GDMi), 33 women with a history of GDM without insulin treatment during pregnancy (GDM), and 45 women after a normoglycemic pregnancy (Ctrl) participating in the ongoing observational PPSDiab study were analyzed by flow cytometry for markers of ILC subsets at the baseline visit (3-16 months postpartum; Visit 1) and 5 years postpartum (58-66 months postpartum; Visit 2).ResultsDuring the first 5 years postpartum, 18 women of the GDMi group (42.8%), 10 women of the GDM group (30.3%), and 8 participants of the Ctrl group (17.8%) developed prediabetes, respectively. Total circulating type 1 innate lymphoid cells (ILC1s) and NK cell numbers as well as percent HLA-DR+ ILC1s were increased in GDMi versus GDM and Ctrl women both at the baseline visit and the 5-year follow-up. Although ILC subsets at Visit 1 could not predict the progression from GDM to prediabetes, ILC2 frequency was associated with insulin sensitivity index (ISI), whereas percent HLA-DR+ ILC1s were inversely correlated. Moreover, circulating leukocytes and total NK cells were associated with waist circumference and fat mass both at Visit 1 and Visit 2.DiscussionOur findings introduce human ILCs as a potential therapeutic target deserving further exploration.Trial registrationStudy ID 300-11.